Wireless power transfer system using series-series compensation topology - Gathageth, Muaad; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Abdul Malik, Noreha; Abd Rahman, Faridah; Ahmed, Muhammed Zahradeen (IEEE, 2021)
Wireless power transfer (WPT) system becomes a truthful technique to avoid cabling and the hazards of electric shock rather than the limitations of plugs compared to the number of devices in any place. In addition, the flexibility of using such technology is way comfortable than the classic way of connecting devices into the charger, where it is obvious that from the mechanism of wirelessly charging itself when the device it is just placed or unplaced to be charged or not, otherwise plug or unplug for charging the devices. Furthermore, Internet of Things IoT interfering in the technology with its all strength and become popular, so all the devices that used this technique need to be wirelessly charged to be in the same line with the need of them along with taking in consideration the usage of these devices as long as it is possible. Thus, this paper presents a comprehensive view of WPT system inductively coupled with some mathematical model derivation for some basic compensations and design of a system that has high power transfer efficiency with constant voltage and constant current as well by compensating the inductive coils with some basic compensations. Also, focuses on the delivery of power stability over vibrations of distances.